1999
DOI: 10.1021/es980736k
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate Formation from Gaseous CO2 and Water

Abstract: Economics of creating CO 2 hydrate on a large scale favor use of gaseous rather than liquid CO 2 as input to the production process. We accordingly studied systems using deionized water and CO 2 gas to reduce formation pressures and costs of hydrate production to the greatest extent possible. Three research avenues were explored: utilization of hysteresis effects, use of dissolved Snomax (a protein from the bacterium Pseudomonas syringae), and development of a continuous flow reactor (cfr) utilizing vigorous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Two major bottlenecks for industrial applications of these materials are (a) the lower weight percentage and (b) regeneration of the captured gas. The hydrate formation from water and gaseous CO 2 was reported by North et al, where these authors observed the growing hydrate crystals optically and by means of calorimetric methods . X-ray diffraction studies showed the time-resolved macroscopic hydrate formation in the stirred water–CO 2 bulk mixture .…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Two major bottlenecks for industrial applications of these materials are (a) the lower weight percentage and (b) regeneration of the captured gas. The hydrate formation from water and gaseous CO 2 was reported by North et al, where these authors observed the growing hydrate crystals optically and by means of calorimetric methods . X-ray diffraction studies showed the time-resolved macroscopic hydrate formation in the stirred water–CO 2 bulk mixture .…”
Section: Introductionmentioning
confidence: 65%
“…The hydrate formation from water and gaseous CO 2 was reported by North et al, where these authors observed the growing hydrate crystals optically and by means of calorimetric methods. 13 X-ray diffraction studies showed the time-resolved macroscopic hydrate formation in the stirred waterÀCO 2 bulk mixture. 14 A combined experimental and molecular dynamics study has provided the first unambiguous evidence for the formation of CO 2 gas hydrates at molecular length scales.…”
Section: ' Introductionmentioning
confidence: 97%
“…The differences in formation conditions between the present data and others might be due to the fact that liquefied CO 2 was not used in this study as is often the case in the literature. 29,30 The studies that examined hydrate for- mation from gaseous CO 2 show higher pressure ranges at ambient temperature 31,32 and at low temperatures based on the injection of gaseous CO 2 on ice crystals. 33 The present method is different from those employed in these studies, because the crystallization of the icehydrate mixture is initiated by a short stirring period of a supercooled CO 2 -saturated solution at low temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is likely to have the cases where CO 2 hydrates are not easy to form 36,37 ; hydrates lighter than water are formed and°oat as observed by Unruh and Katz 38 and North et al 39 North et al 39 pointed out, based on their experimental observations, that only the freshly formed CO 2 hydrate in water is lighter than water and the matured CO 2 hydrate is heavier than water. With even lower value of molar fraction of CO 2 in the CO 2 hydrate, unstable paste-like CO 2 hydrate composite will be formed.…”
Section: Density Of Co 2 Hydrate Slurry and Solid Mass Fractionmentioning
confidence: 97%